Uganda - The Contribution Of Indigenous Vegetables to Household Food Security - Rubaihayo, E.B. (World Bank, Washington, DC, 2012)
The note aims to prompt policy makers, and development managers to reassess, and give more weight to neglected production, and consumption of traditional vegetables, so as to enhance nutrition, income generation, and food security for small scale households. Though the views expressed herewith are the results of interviews in several African countries, it focuses mainly on the Uganda situation. The contribution of indigenous vegetables to household food security, namely, kitchen gardens common in urban centers, or home gardens found in villages, is characterized by intercropping systems, a food production strategy which has been overlooked by both policy makers, and extension specialists. The importance of traditional vegetables, such as cowpeas, cabbage, amaranthus, and solanum aethiopicum, is emphasized, to provide and meet the daily requirements of vitamins, minerals, and proteins. However, there is reduced effectiveness in ensuring food security all year round, due to the fact that very few traditional vegetables are cultivated, and in Uganda, rural women have limited access to resources. Thus, the note stipulates that extensive education on the importance of balanced food nutrition -as well as direct or indirect source of income if home grown - particularly for the resource-poor families, must be undertaken by African governments.